Efektivitas Islamic Hypnotherapy untuk Menurunkan Stres pada Remaja Akhir - Zahro Varisna Rohmadani; Andhita Dyorita Khoiryasdien (JIP (Jurnal Intervensi Psikologi), 2022)
Mental health in adolescence vulnerable to decline during the covid-19 pandemic. They are the next generation of the nation, where the success of a country can be seen from the quality of the nation, adolescents have a big role as agents of change. This research focused on knowing the effectiveness of Islamic Hypnotherapy in reducing stress in adolescents during the Covid-19 pandemic. The research design used two groups, namely the control and experimental groups. The research subjects were 58 adolescents who indicated stress with high and very high scores based on the DASS scale survey. The data analysis method used is nonparametric statistical analysis with the Wilcoxon Signed Rank Test to test the differences in the pre-test and post-test conditions in one group and Mann Whitney U Test to test the differences between the two groups, using SPSS 21 for Windows. The results showed that p = 0.004 which means p < 0.05. This shows that there is a difference between the experimental group and the control group. Islamic Hypnotherapy can have a stress-reduction effect of 53.74. So it can be concluded that Islamic Hypnotherapy is effective for reducing stress in adolescents during the Covid-19 pandemic.